Statistic Analysis of Slavonic and Baltic Etymological Equivalents (according to the Data of Słownik prasłowiański) - Ušinskienė, Viktorija (Slavistica Vilnensis, 2009)
The article presents the results of preliminary statistic and semantic analyses of the Slavonic and Baltic etymological equivalents according to the data of Słownik praslowiański. The analysis was based on one hundred and seven Baltic-Slavonic noun equivalents and the semantic classification of the collected material. Markowski’s system of ideographic distribution was used for this purpose. All material were divided into fifty thematic groups that consisted of six semantic spheres and two macro-spheres, such as ME (PERSON) and THE WORLD BEYOND ME. The analysis conducted allows the author to point out that a remarkable majority of Slavonic and Baltic etymological equivalents describe the external world, of either animate or inanimate nature (i. e. the macro-sphere THE WORLD BEYOND ME). Respectively, the semantic field THE WORLD turned out to be the most representative. In terms of the number of equivalents, the fields MY BODIES and the field IT THAT SERVES MY BODY occupy the next two positions. A significant number of equivalents characterize the thematic groups of agriculture and daily life. Contrary to the author’s expectations, the groups of family attitudes and emotions have appeared 10 have a similar number of equivalents, although in general the words referring to the spiritual and mental life of a person are not numerous.